1999
DOI: 10.1073/pnas.96.11.6501
|View full text |Cite
|
Sign up to set email alerts
|

Heterothermal acclimation: An experimental paradigm for studying the control of thermal acclimation in crabs

Abstract: A method for the study of the control of the attainment of thermal acclimation has been applied to the crabs, Cancer pagurus and Carcinus maenas. Crabs were heterothermally acclimated by using an anterior-posterior partition between two compartments, one at 8°C and the other at 22°C. One compartment held a three-quarter section of the crab including the central nervous system (CNS), eye stalks, and ipsilateral legs; the other held a quarter section including the contralateral legs. Criteria used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Some 10 years ago we carried out a novel experimental paradigm that sought to establish whether responses made by crabs to a change in acclimation temperature were directed by the CNS and hormonal systems (Cuculescu et al, 1999;Pearson et al, 1999). This aim was prompted by the earlier proposals of Prosser et al (1965), Lagerspetz (1974) and Prosser and Nelson (1981) that the CNS played a dominant role in acclimation to temperature in poikilotherms, furthermore Silverthorne (1975) showed a hormonal involvement in thermal acclimation of fiddler crab respiration.…”
Section: Introductionmentioning
confidence: 98%
“…Some 10 years ago we carried out a novel experimental paradigm that sought to establish whether responses made by crabs to a change in acclimation temperature were directed by the CNS and hormonal systems (Cuculescu et al, 1999;Pearson et al, 1999). This aim was prompted by the earlier proposals of Prosser et al (1965), Lagerspetz (1974) and Prosser and Nelson (1981) that the CNS played a dominant role in acclimation to temperature in poikilotherms, furthermore Silverthorne (1975) showed a hormonal involvement in thermal acclimation of fiddler crab respiration.…”
Section: Introductionmentioning
confidence: 98%
“…Rather, we took advantage of the fact that ectotherm membrane fluidity changes in response to environmental temperature (Cossins and Prosser, 1978;Hazel, 1995;Hazel and Williams, 1990;Hochachka and Somero, 2002;McElhaney, 1984;Sinensky, 1974). Alteration of ectotherm membrane fluidity by modulating environmental temperature is well established (Cossins et al, 1981;Cossins and Prosser, 1978;Los and Murata, 2004;Sinensky, 1974), and this approach has been used to investigate membrane acclimation and adaptation in E. coli (Sinensky, 1974), cyanobacteria (Horvath et al, 1998;Los et al, 1993;Los and Murata, 2004;Vigh et al, 1998), crayfish (Pruitt, 1988), crabs (Cuculescu et al, 1999) and fishes (Cossins and Prosser, 1978;Hazel and Landrey, 1988;Hazel et al, 1998;Tiku et al, 1996;Zehmer and Hazel, 2003). The dramatic increase in tolerance that accompanied the inferred increase in membrane order suggests that modification of membrane physiology to counter the membrane-disrupting effects of ethanol could be as important as toxin metabolism in determining ethanol tolerance in Drosophila.…”
Section: Membrane Physiology In Response To Both Environmentalmentioning
confidence: 99%
“…Seasonal activity levels have been shown to alter the muscle phenotypes in crustaceans, for example, in crayfish, Lnenicka (1993) and Atwood and Nguyen (1995) have reported that phasically innervated muscle in winter becomes more tonic in summer. Changes in membrane fatty acid composition and fluidity, commonly reported to be associated with thermal acclimation (Cuculescu et al 1999), may also be a factor in the seasonal dependency.…”
Section: Ejp Amplitudementioning
confidence: 99%